ACUPUNCTURE TREATMENT OF FACIAL PALSY - Bokhari, Syed Zahid Hussain; Zahid, Syeda Samina (Journal of Ayub Medical College Abbottabad, 2010)
Background: Bell's palsy is an idiopathic, acute peripheral-nerve palsy involving the facial nerve which supplies all the muscles of facial expression. This study was conducted to evaluate the effects of Electro-Acupuncture on patients with Facial Palsy. Methods: This study was conducted on patients with facial palsy at a private clinic at Peshawar during 1999-2009, and 49 cases were included in the study. All those cases that were within first two weeks of illness or who had related history of stroke or they had upper motor neuron lesion were not included in the study. Electroacupuncture was used as the main therapeutic technique to treat these cases. Patients were subjected to acupuncture treatment at four major points on the face for 20-25 minutes everyday for 10 days. Specific points were used for nasolabial fold and watering of the eye. After rest for a week patients were again evaluated and another course of treatment comprising of 5-10 days was sufficient in most cases. Frequency of electro-acupuncture is kept at 60-80 cycles per minute. Results: Total number of patients studied was 49 with duration of illness as early as 3 weeks to a year and above. Cases with duration of illness from 3 weeks onward showed rapid recovery of palsy symptoms with electro-acupuncture. All cases showed recovery. Palsy of the angle of the mouth did not recover completely. Conclusion: Electro-acupuncture is effective in treating facial palsy cases. Keywords: Facial palsy, Bell's palsy, Electro-acupuncture